2013
DOI: 10.1002/wrcr.20486
|View full text |Cite
|
Sign up to set email alerts
|

Permeability evolution due to dissolution and precipitation of carbonates using reactive transport modeling in pore networks

Abstract: [1] A reactive transport model was developed to simulate reaction of carbonates within a pore network for the high-pressure CO 2 -acidified conditions relevant to geological carbon sequestration. The pore network was based on a synthetic oolithic dolostone. Simulation results produced insights that can inform continuum-scale models regarding reactioninduced changes in permeability and porosity. As expected, permeability increased extensively with dissolution caused by high concentrations of carbonic acid, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
109
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 64 publications
2
109
0
Order By: Relevance
“…These include: the mixed-cell method (MCM) [e.g., Acharya et al, 2005;Bryntesson, 2002;Kim et al, 2011;Li et al, 2006;Mehmani et al, 2012;Nogues et al, 2013], random walk [e.g., Sorbie and Clifford, 1991;Bruderer and Bernabe, 2001;Bijeljic et al, 2004;Jha et al, 2011], smoothed particle hydrodynamics (SPH) [e.g., Zhu and Fox, 2002], lattice Boltzmann (LB) [e.g., Kang et al, 2006], and classical Computational Fluid Dynamics (CFD) [e.g., Shen et al, 2011]. In this work, we employ MCM because of its overall simplicity and computational efficiency.…”
Section: Flow and Transport In Network Modelmentioning
confidence: 99%
“…These include: the mixed-cell method (MCM) [e.g., Acharya et al, 2005;Bryntesson, 2002;Kim et al, 2011;Li et al, 2006;Mehmani et al, 2012;Nogues et al, 2013], random walk [e.g., Sorbie and Clifford, 1991;Bruderer and Bernabe, 2001;Bijeljic et al, 2004;Jha et al, 2011], smoothed particle hydrodynamics (SPH) [e.g., Zhu and Fox, 2002], lattice Boltzmann (LB) [e.g., Kang et al, 2006], and classical Computational Fluid Dynamics (CFD) [e.g., Shen et al, 2011]. In this work, we employ MCM because of its overall simplicity and computational efficiency.…”
Section: Flow and Transport In Network Modelmentioning
confidence: 99%
“…Reactive transport modeling has been previously used to investigate geochemical reactions and their effects on permeability and porosity evolution [14,15,[23][24][25][26]. André et al [14] simulated CO 2 storage in the carbonate-rich Dogger aquifer in the Paris Basin (France) using the reactive transport simulator TOUGHREACT.…”
Section: Introductionmentioning
confidence: 99%
“…This was in accordance with the reactive flow-through experimental study by Luquot and Gouze [15] for the same basin. Some studies [25,26] also reported that geochemical reactions dissolved the host rock increasing porosity and permeability thereby affecting fluid flow through reactive transport modeling. On the other hand, Izgec et al [23] found that CO 2 injection into carbonate aquifers simulated using CMG's STARS could result in permeability reduction as well as improvement depending on the balance between mineral dissolution and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…xCT imaging has been used to provide valuable insights in core-flow experiments designed to investigate fractures in the context of geohydrological, geochemical, and geomechanical processes of the deep subsurface, such as CO 2 geological storage [20,30,40] and oil and gas operations [13-15, 17, 41-46]. Quantitative characterizations of fracture geometries have advanced our understanding of fracture hydrodynamics [13,17,21,[47][48][49], reactivity [11,24,25,35,36,47,[50][51][52][53], and mechanics [16,19,37].…”
Section: Introductionmentioning
confidence: 99%